Ответ:
![\frac{3}{8}x\leq - \frac{3}{4} \frac{3}{8}x\leq - \frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7Dx%5Cleq%20-%20%5Cfrac%7B3%7D%7B4%7D)
умножим обе части неравенства на ![image](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B3%7D%3C%2Fp%3E%3Cp%3E%20%5Btex%5D%5Cfrac%7B8%7D%7B3%7D%2A%20%5Btex%5D%5Cfrac%7B3%7D%7B8%7Dx%5Cleq%20%20%28-%5Cfrac%7B3%7D%7B4%7D)
[tex]\frac{8}{3}* [tex]\frac{3}{8}x\leq (-\frac{3}{4}" alt="\frac{8}{3}
[tex]\frac{8}{3}* [tex]\frac{3}{8}x\leq (-\frac{3}{4}" align="absmiddle" class="latex-formula"> )* [tex]\frac{8}{3}
затем сокращаем то что можно сократить и получаем
х≤-2
Объяснение: